Foreword - Šteinberga, Airisa (History of Engineering Sciences and Institutions of Higher Education, 2020)
The fourth issue of the scientific journal prepared by the RTU Research Centre for Engineering History (RCEH) comprises seven studies on Riga Polytechnicum (RP) / Riga Polytechnic Institute (RPI) students, graduates, lecturers and issues related to engineering sciences. The authors of the scientific publications are Latvian scientists, historians of science, museologists, and pedagogues. The articles are mainly based on the presentations made at the RTU 60th International Scientific Conference on 10 October 2019. The research topics are the activities of RP / RPI students, graduates and lecturers, the history of engineering sciences and associations